IMPLEMENTASI KEBIJAKAN PEMUTAKHIRAN DATA MANDIRI APARATUR SIPIL NEGARA MELALUI APLIKASI MYSAPK PADA BADAN KEPEGAWAIAN DAERAH PROVINSI KALIMANTAN BARAT - Intan Dwi Lestari; Bakran Suni (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2022)
This study aims to find out and analyze the process of implementing the Independent Data Updating Policy for State Civil Apparatus through the MySAPK Application at the Regional Personnel Agency of West Kalimantan Province because there are still many State Civil Apparatuses who have not updated their independent data or are still incorrectly filling out independent data updating through the MySAPK application. the. The theory used in this study was the theory proposed by Charles O. Jones about the policy implementation process. This study used the qualitative method with descriptive research. The results showed that the Implementation of the Independent Data Updating Policy for State Civil Apparatus Through the MySAPK Application at the Regional Personnel Agency of West Kalimantan Province has been running but not yet optimal because there are still problems in policy implementation. It was proven by a) Organization; the absence of the Organizational Structure and Work Procedures which were created for a clear division of tasks and responsibilities; furthermore, the facilities and infrastructure supporting the policy program have not been optimized, such as the internet network and the MySAPK application which is still frequently maintained; b) Interpretation; the consistency of users and officers in delivering information on program implementation is still low and there is a lack of socialization and assistance; c) Applications; lack of monitoring and evaluation of the program by the Responsible Officer and staff. Recommendations from this research are: 1) There should be improvements or additions to facilities and infrastructure that serve to support the implementation of the policy, such as making an MOU to increase internet bandwidth in overcoming internet network problems; 2) Applying reward and punishment as a tool for fostering and monitoring users so as to increase seriousness and awareness in implementing the independent data updating policy; 3) There should be a gradual implementation of monitoring/supervision by the Officer in Charge so that periodic policy evaluations can be carried out. Keywords: Implementation, MySAPK Application, Independent Data Updating